International Law versus Piracy: Issues in Legal Theory - N. Vylegzhanin, Alexander; S. Anyanova, Ekaterina (International Journal of Psychosocial Rehabilitation, 2020)
The article examines the theoretical framework of interpreting the existing rules of international customary and treaty law applicable to the repression of piracy. The main characteristics of crime “piracy” are their focus on the high seas or to the exclusive economic zone (EEZ), or to another place “outside jurisdiction of any State” and the crime of piracy is committed for “private ends” by a “private” ship or aircraft against another ship (or other ships). Such criteria are provided, in concreto, in art. 100 of the UN Convention on the Law of the Sea (UNCLOS). However, interpretation of UNCLOS rules on piracy raises questions. While addressing them, this paper contains an executive summary of problems concerning piracy in the context of applicable norms of international law making special emphasis on the necessity to respect relevant customary rules. In this context, the paper examines questions such as the legal concept of piracy in historical perspective; the “humanitarian” attitude towards pirates, suggested in UNCLOS; States’ conduct of anti-piracy operations; various interpretations of conventional terms, including “for private ends” and “against another ship”; current enforcement measures against piracy; and examination of other theoretical issues in the legal combat against piracy. In addition to introducing key elements of analysis and the results, the paper reviews rationales for related research studies and existing literature on the subject. This review is followed by focus on the research methodology and procedures used in the study and a discussion of data analysis techniques. Special attention is also paid to existing gaps in legal research as well as to inconsistencies and/or controversies in applicable treaty rules or in relevant legal teachings. A conceptual framework explaining the main findings and the results of this enquiry are summarized. Examples of piracy attacks provided in the article include their statistics, while highlighting that only about half of piracy attacks and relevant damage to ship-owners is officially reported. The paper also addresses managerial implications, limitations and directions for further research on the topic under investigation. The article ends with an appropriate conclusion and references.